Mechanism of TAp73 inhibition by ΔNp63 and structural basis of p63/p73 hetero-tetramerization. - Gebel, J; Luh, L; Coutandin, D; Osterburg, C; Löhr, F; Schäfer, B; Frombach, A; Sumyk, M; Buchner, L; Krojer, T; Salah, E; Mathea, S; et al. (Nature Publishing Group, 2016)
Members of the p53 tumor suppressor family are expressed as multiple isoforms. Isoforms having an N-terminal transactivation domain are transcriptionally active while those ones lacking this domain often inhibit the transcriptional activity of other family members. In squamous cell carcinomas, the high expression level of ΔNp63α inhibits the tumour suppressor function of TAp73β. This can in principle be due to blocking of the promotor or by direct interaction between both proteins. P63 and p73 can hetero oligomerize through their tetramerization domains and a hetero-oligomer consisting of two p63 and two p73 molecules is thermodyna mically more stable than both homo tetramers. Here we show that hetero tetramer complexes exist also in differentiating keratinocytes. Through structure determination of the hetero tetramer we reveal why this hetero tetramer is the thermodynamically prefer red species. Based on this structure we have created mutants that either enable the formation of only heterotetramers or only homotetramers, allowing to investigate the function of these heterotetramers. Using these tools we show that inhibition of TAp73β in squamous cell carcinomas is due to promotor squelching and not direct interaction.